Kif5B and Kifc1 Interact and Are Required for Motility and Fission of Early Endocytic Vesicles in Mouse Liver - Nath, Sangeeta; Bananis, Eustratios; Sarkar, Souvik; Stockert, Richard J.; Sperry, Ann O.; Murray, John W.; Wolkoff, Allan W. (East Carolina University, 2007)
Early endocytic vesicles loaded with Texas Red asialoorosomucoid were prepared from mouse liver. These vesicles bound to microtubules in vitro, and upon ATP addition, they moved bidirectionally, frequently undergoing fission into two daughter vesicles. There was no effect of vanadate (inhibitor of dynein) on motility, whereas 5"-adenylylimido-diphosphate (kinesin inhibitor) was highly inhibitory. Studies with specific antibodies confirmed that dynein was not associated with these vesicles and that Kif5B and the minus-end kinesin Kifc1 mediated their plus- and minus-end motility, respectively. More than 90% of vesicles associated with Kifc1 also contained Kif5B, and inhibition of Kifc1 with antibody resulted in enhancement of plus-end–directed motility. There was reduced vesicle fission when either Kifc1 or Kif5B activity was inhibited by antibody, indicating that the opposing forces resulting from activity of both motors are required for fission to occur. Immunoprecipitation of native Kif5B by FLAG antibody after expression of FLAG-Kifc1 in 293T cells indicates that these two motors can interact with each other. Whether they interact directly or through a complex of potential regulatory proteins will need to be clarified in future studies. However, the present study shows that coordinated activity of these kinesins is essential for motility and processing of early endocytic vesicles. Originally published Molecular Biology of the Cell, Vol. 18, No. 5, May 2007
Keywords: Endocytic vesicles; Mouse liver; Kif5B; Kifc1